Formulasi Nanopartikel Losartan dengan Pembawa Kitosan - AKHMAD KHARIS NUGROHO; NURI ARI EFIANA; RONNY MARTIEN (Fakultas Farmasi Universitas Pancasila, 2013)
Nanoparticle formulation is important for systemic drug delivery via several routes. This research was aimed to establish optimal formation of chitosan nanoparticle formulation with losartan, an antihypertension known as an angiotensin II receptor antagonist. Ionic gelation method was used. Formulation was established in 2 steps. Firstly, determination of the best losartan and chitosan concentrations which can produce physically stable nanoparticles without precipitation, at room temperature within 25 days. Secondly, optimization of the process by factorial design method of two factors, including pH (4.0 and 5.0) and the stirring rate (350 and 700 rpm), with the loading capacity of the nanoparticle as the observed response. The obtained nanoparticles were evaluated further for its particle size and zeta potential. The physichal stability tests indicated that two nanoparticle formulations containing losartan-chitosan of (14 mg% : 35 mg%), and losartan-chitosan of (21 mg% : 35 mg%) were stable. The factorial design studies suggested that pH 4 and the stirring rate of 350 rpm were the optimal conditions which produced the highest loading capacity (47,7%). The particle size and zeta potential of the stable nanoparticle were 290.3±52.6 nm and +50.8 ±4.8 mV respectively.